Performance and evaluation of graphite when machining hardened steel ASSAB 718 - Saeed Ahmed, Radwan Ahmed (2009)
This project presents the machining of ASSAB718 hardened steel using sinker electro-discharge machining involving two different graphite electrodes. POCO EDM4 and POCO EDM200 The main purpose of this study was to investigate the influence of various parameters on the machining characteristics, namely, surface roughness (Ra), Material removal rate (MRR), Electrode wear rate (EWR), and Microcracks depth after undergoing sinker EDM process. The Full Factorial Design of Experiment (DOE) approach with two-levels was used to formulate the experimental plan and, to analyze the effect of each parameter on the machining characteristics four factors under study were pulse interval (A), pulse duration on (R), peak current (P) and servo voltage (SV). Confirmation tests were conducted for the optimum conditions for each machining characteristics in order to verifying and comparing. Design Expert software was utilized to analyze the above results. The, servo voltage and pulse of signal have appeared to be significant to all responses investigated. Overall, the results from the confirmation tests showed that the percentage of performance was acceptable due to all the results obtained were within the allowable value which was less than 11% of margin error for EDM200 and 7.23% for EDM4 electrodes respectively.